Pathomorphology Changes In The Colon Mucosa During A Protein-Loaded Diet (Texas Journal of Medical Science, 2025)
An incrense of consumption of proteins in dagly ration with other nutrients, or getting a big amount of proteins to the organism lends to the negative results. Assimilated proteins as metrients can not be assumulated in organism as a reserve.Exess of proteins turn info glucose in liver forming trasitional substanus harm ful for the human organism. Hove over, excess of proteins incrense the aciditg of urine and leads to the osteoporosys. Due to the relense of la from bones. Hystostructural shitts of mucosa of colon as a result of processes mentioned abore have also bun studies.